2006
DOI: 10.1074/jbc.m603921200
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Interaction between Sprouty Proteins and Caveolin-1

Abstract: Growth factor-mediated signal transduction cascades can be regulated spatio-temporally by signaling modulators, such as Sprouty proteins. The four mammalian Sprouty family members are palmitoylated phosphoproteins that can attenuate or potentiate numerous growth factor-induced signaling pathways. Previously, we have shown that Sprouty-1 and Sprouty-2 associate with Caveolin-1, the major structural protein of caveolae. Like Sprouty, Caveolin-1 inhibits growth factor-induced mitogen-activated protein kinase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…In addition, the analysis showed that both Spry2 and DYRK1A are present in the crude synaptosomal fraction, preferentially associated with the synaptic plasma membranes. Whereas Spry2 has been reported to localize to the plasma membrane through palmitoylation and/or caveolin binding (7,28), nothing about DYRK1A membrane association has been reported or inferred from its primary structure. DYRK1A distribution in VOL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the analysis showed that both Spry2 and DYRK1A are present in the crude synaptosomal fraction, preferentially associated with the synaptic plasma membranes. Whereas Spry2 has been reported to localize to the plasma membrane through palmitoylation and/or caveolin binding (7,28), nothing about DYRK1A membrane association has been reported or inferred from its primary structure. DYRK1A distribution in VOL.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether palmitoylation of Spry proteins is a dynamic process regulated by stimulation of cells with growth factors remains to be determined. Finally, Spry proteins may translocate to plasma membranes via interactions through their C-terminal regions with caveolin-1 after serine phosphorylation in response to growth factor stimulation (Impagnatiello et al, 2001;Cabrita et al, 2006). Whatever the mechanism, it is clear that translocation of Spry1 and Spry2 is necessary for inhibition of growth factor-stimulated cell migration, proliferation, and differentiation by Spry proteins (Yigzaw et al, 2001).…”
Section: Regulation Of Biological Processes By Spry Proteinsmentioning
confidence: 99%
“…Kajita et al have shown that overexpression of SPRY2 inhibited PDGF-induced ERK1/2 activity in dense, but not in sparse NIH 3T3 fibroblast cell cultures [171]. In a similar fashion, SPRY2 function in T47D breast carcinoma cells also depended on cell density [157].…”
Section: Spry2 Expression Controls Monolayer Integrity and Quiescencementioning
confidence: 74%
“…Several overexpressing studies [10,126,157] and SPRY2 knockout mice [151,[153][154][155] confirmed its potential as a negative regulator of several RTK-related signaling pathways. However, the endogenous expression pattern(s) of SPRY2 remain not well delineated, and it is unknown whether SPRY2 function regulates endothelial quiescence.…”
Section: Rationale and Aimsmentioning
confidence: 96%
See 1 more Smart Citation